2019
DOI: 10.1016/j.jaci.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to apoptosis underpins the corticosteroid insensitivity of group 2 innate lymphoid cells

Abstract: TSLP.To test the hypothesis that absence of keratins in KtyI 2/2 cells upregulates TSLP through stimulation of EGFR, growth factor-starved WT and KtyI 2/2 cells were treated for 3 and 7 hours with 200 ng/mL recombinant AREG, followed by TSLP mRNA and protein analysis. This revealed a strong induction of Tslp mRNA in WT and KtyI 2/2 cells caused by the AREG stimulus (Fig 2 , A), with greater Tslp mRNA levels in KtyI 2/2 cells. Interestingly, AREG-EGFR stimulation of TSLP protein by 4-fold was restricted to KtyI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Patients with neutrophilic asthma usually have poor response to corticosteroids [ 34 36 ], and our previous study has found that the numbers of ILC3s in asthma patients were not reduced after treatment with prednisolone [ 23 ]. Therefore, we speculated that ILC3s might contribute to the steroid resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with neutrophilic asthma usually have poor response to corticosteroids [ 34 36 ], and our previous study has found that the numbers of ILC3s in asthma patients were not reduced after treatment with prednisolone [ 23 ]. Therefore, we speculated that ILC3s might contribute to the steroid resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were cultured in RPMI with 10% human serum, 1× l -glutamine, 1× penicillin/streptomycin, 1× sodium pyruvate, 1× nonessential amino acids, and 250 U/mL IL-2. Details were described in our previously published study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some limited evidence supports the notion that ILC2s may help mediate steroid-resistant asthma. Thus, Nagakumar et al found that steroid-resistant asthma patients bear more sputum ILC2s than control asthma patients 9 , while Luo et al reported circulating ILC2s from steroid-resistant asthma patients rose after steroid treatment, unlike Th2 cells 34 . Moreover, van der Ploeg et al observed that asthma patients have more in ammatory CD45RO + ILC2s in the in amed mucosal tissues and blood of asthma patients than controls and that these ILC2 frequencies correlate with disease severity and steroid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al found that peripheral blood ILC2s from healthy subjects express higher levels of the antiapoptotic genes BCL2 and BCL2L1 and lower levels of the pro-apoptotic genes BAX1 and BAK1 than Th2 cells. Since the ILC2s but not the Th2 cells were resistant to steroids, this suggests that ILC2s are less sensitive to the pro-apoptotic effects of steroids than Th2 cells 34 and TSLP together convert CD45RA + ILC2s, which are steroid-sensitive, into steroid-resistant CD45RO + ILC2s in vitro; TSLP on its own did not have this effect 35 . Kabata et al observed that steroid-sensitive murine ILC2s became steroid-resistant when they were stimulated in vitro with both IL-33 and TSLP 10 .…”
Section: Discussionmentioning
confidence: 99%
“…IFNγ, or Th2 cell resistance to apoptosis ( Huang et al, 2001 ; Williams et al, 2018 ). Additionally, ILC2 activation, which promotes type 2 inflammation, could also contribute to enhanced allergic airway inflammation and corticosteroid insensitivity ( Luo et al, 2019 ). ILC2 regulation involves negative regulatory signals from IFNγ or PGE 2 ( Duerr et al, 2016 ; Maric et al, 2018 ; Zhou et al, 2018 ; Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%